Video games and violence among children and adolescents in the Arab world: A systematic review : Video games and violence in Arab world - AlHazzaa, Shahad A.; Alwohaibi, Rawaa N.; AlMusailet, Latifah I.; Alshrefy, Afnan J.; Almaimoni, Reema A.; Menezes, Ritesh G. (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Video gaming has witnessed tremendous growth in recent years. Video games have been associated with various negative effects on players, such as aggressive behavior and reduced apathy. The present review aims to investigate the association between video games and violence among children and adolescents in the Arab world, while highlighting the influence of the type of video games played, time spent playing, and other possible associated factors.Methods: A literature search was performed on PubMed and Web of Science electronic databases. All studies assessing video games and violence among children and adolescents written in English were eligible for inclusion in the review. A total of 9 studies were included in this systematic review. Results: Six studies investigated the relationship between video games and aggression, five of which found a significant association. Several factors have been studied to assess their role in mediating the association between the two. A statistically significant association was found between aggression and age and sex of the players, with a predominance among early adolescents and males. Longer durations spent playing video games were found in three studies to be significantly associated with a greater risk of aggression. Conclusions: In the Arab world, studies addressing this subject are limited. The discrepancy of reported results between video games and amount of violence could be attributed to the lack of standardization across studies. Therefore, it becomes imperative to further explore the association through conclusive studies with standardized measures.(www.actabiomedica.it)